2021
DOI: 10.3390/en14175277
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Design of an Axial-Flow Turbine for Small-Scale Supercritical Organic Rankine Cycle

Abstract: A small-scale organic Rankine cycle (ORC) with kW-class power output has a wide application prospect in industrial low-grade energy utilization. Increasing the expansion pressure ratio of small-scale ORC is an effective approach to improve the energy efficiency. However, there is a lack of suitable expander for small-scale ORC that can operate with a high efficiency under the condition of large expansion pressure ratio and small mass flow rate. Aiming at the design of high-efficiency axial-flow turbine in smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Peng et al [6] investigated the performance of a kilowatt-class axial-flow turbine and proposed a method for improving the turbine efficiency. The preliminary design of the axial-flow turbine was performed for parameter optimization, and the effect of the tip clearance and trailing edge thickness on the turbine performance was analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al [6] investigated the performance of a kilowatt-class axial-flow turbine and proposed a method for improving the turbine efficiency. The preliminary design of the axial-flow turbine was performed for parameter optimization, and the effect of the tip clearance and trailing edge thickness on the turbine performance was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics (type, number of stages, rotational speed, efficiency, and power output) of the aforementioned turbines and ORC thermal efficiency. In particular, in the case of a single-stage axial turbines of 200 kW or less, high rotational speed (>40,000 rpm) was applied to increase the efficiency [6,[14][15][16]. However, a highrotational-speed turbine requires high-performance bearings such as frictionless bearings.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that turbine power at nominal total expansion ratio at 3.9 is 71.2 kW. Peng et al [13] investigated the performance of a kW-class multi-stage axial turbine, which is suitable for a small-scale ORC. In particular, the off-design for turbine performance was performed using parameters such as the number of turbine stages, trailing edge thickness, and tip clearance.…”
Section: Introductionmentioning
confidence: 99%